A case of improvement of clozapine-induced low leukocyte counts by adenine, cepharanthin and ninjin-yoei-to in a patient with treatment-resistant schizophrenia - Shintaro Kamei (BMC, 2021)
Abstract Background Although clozapine is the optimal drug for patients with treatment-resistant schizophrenia, the drug has harmful adverse effects such as leukopenia. Adenine and cepharanthine are known to be effective for radiation- or drug-induced leukopenia. Furthermore, ninjin-yoei-to, a Chinese herbal medicine, augments the production of granulocyte-macrophage colony-stimulating factor. Thus, these drugs may be useful for clozapine-induced leukopenia. Case presentation A 21 years-old woman with schizophrenia was hospitalized for initiation of clozapine treatment. Despite concomitant use of adenine, cepharanthine, and lithium carbonate having activities of increasing leukocytes, a decrease in leukocyte counts occurred after the initiation of clozapine. Additional administration of ninjin-yoei-to increased leukocyte counts, which prevented the development of leukopenia. Conclusions This is the first case that concomitant use of adenine, cepharanthin, and ninjin-yoei-to exhibited the effectiveness of reversing the decrease in leukocytes caused by clozapine. Monitoring leukocyte counts and preventing leukopenia are essential for successful treatment with clozapine for refractory schizophrenia. These medicines may be a potential option for preventing clozapine-induced leukopenia.